2018
DOI: 10.3762/bjnano.9.51
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of fluorescent carbon dots from spices for in vitro imaging and tumour cell growth inhibition

Abstract: Carbon dots have demonstrated great potential as luminescent nanoparticles in bioapplications. Although such nanoparticles appear to exhibit low toxicity compared to other metal luminescent nanomaterials, today we know that the toxicity of carbon dots (C-dots) strongly depends on the protocol of fabrication. In this work, aqueous fluorescent C-dots have been synthesized from cinnamon, red chilli, turmeric and black pepper, by a one-pot green hydrothermal method. The synthesized C-dots were firstly characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(76 citation statements)
references
References 50 publications
(54 reference statements)
3
72
1
Order By: Relevance
“…Recently, researchers have found that some of the CDs using green carbon sources including green tea, garlic, pepper, lysine and so on or drugs such as aspirin may get both fluorescent characters and bioactivities such as anticancer, antioxidant and anti-inflammatory effects. [30][31][32][33][34] These attractive CDs can show significant bioactivities when they are used for tracing and bioimaging in vivo or vitro. It is a fascinating challenge to form the CDs having both biological activities and fluorescent property after high temperature hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have found that some of the CDs using green carbon sources including green tea, garlic, pepper, lysine and so on or drugs such as aspirin may get both fluorescent characters and bioactivities such as anticancer, antioxidant and anti-inflammatory effects. [30][31][32][33][34] These attractive CDs can show significant bioactivities when they are used for tracing and bioimaging in vivo or vitro. It is a fascinating challenge to form the CDs having both biological activities and fluorescent property after high temperature hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have successfully used the CQDs for in vitro bioimaging. 52,[101][102][103][104][105][106][107][108][109][110][111][112][113] In several applications, the QDs are preferred to organic dyes and uorescent proteins due to the enhanced brightness, photostability, imaging sensitivity, and good resistance to metabolic degradation. 114 Semiconductor QDs such as CdSe with their core-shell structure (e.g.…”
Section: Optical Imagingmentioning
confidence: 99%
“…transform different substrates such as pollen, spices and coffee beans (D'Angelis do ES et al, 2015;Essner et al, 2016;Vasimalai et al, 2018;Zhang et al, 2018). However, converting biomass into biochar with the sole aim of making advanced nanomaterials is a high energy cost process that misses the opportunity for bioenergy production.…”
Section: Accepted Manuscriptmentioning
confidence: 99%